1995
DOI: 10.1016/s0194-5998(95)70178-8
|View full text |Cite
|
Sign up to set email alerts
|

Day care and the incidence of otitis media in young children

Abstract: The total size of the day care group is an important intervening variable in the relationship between attending day care and frequent ear infections for children younger than 12 months. The size of the day care group rather than the day care per se is the primary "modifiable risk variable" for many working parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
3
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 13 publications
2
35
3
2
Order By: Relevance
“…Day care attendance is associated with frequent respiratory infections, some of which are accompanied by AOM. 5,6 Several studies have shown that access to care for children has improved with approximately 90% of parents indicating that their children have a regular source of care. 7,8 We believe that improved access to care is accompanied by increased diagnoses of minor infections and increased oral antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Day care attendance is associated with frequent respiratory infections, some of which are accompanied by AOM. 5,6 Several studies have shown that access to care for children has improved with approximately 90% of parents indicating that their children have a regular source of care. 7,8 We believe that improved access to care is accompanied by increased diagnoses of minor infections and increased oral antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…3 The incidence of AOM is increasing, as evidenced by the doubling of prescriptions written for AOM in the last decade from 12 million in 1980 to 24 million in 1992. 4 This increase in antibiotic usage is likely due to a number of factors, including increase in real disease, due in part to widespread day care attendance, 5,6 improved access to care, 7,8 and overprescription of antibiotics.…”
mentioning
confidence: 99%
“…It has been indicated that early and massive nasopharyngeal colonization with potentially pathogenic bacteria may p1ay a role in the pathogenesis of OM especially in high risk populations (Leach et al 1994, Homøe et al 1996. Risk factors in studies from other parts of the world include race, male gender, cleft palate, young age at first AOM, episode, siblings in the household with URTI, parental history of OM, attendance in large size daycare centers, exposure to passive smoking, lack of breast feeding, feeding position, atopy, prematurity, use of comforter, poor housing standard, and social poverty (i.e., poor living conditions) (Christensen 1956, Howie et al 1975, Strangert 1977, Ingvarsson et al 1982b, Saarinen 1982, Vinther et al 1982, Ståhiberg et al 1986, Fleming et al 1987, Kero and Piekkala 1987, Shapiro 1988, Harsten et al 1989, Teele et al 1989, Alho et al 1990, Froom and Culpepper 1991, Duncan et al 1993, Bastos 1994, Aniansson et al 1994, Ey et al 1995, Marx et al 1995, Sorri et al 1996, Uhari et al 1996, Kvaerner et al 1997aand b, Stenstrom and Ingvarsson 1997a, Daly et al 1999. However, results are conflicting for several of these risk factors, and most have only slightly been found to increase the risk for AOM.…”
Section: Aimsmentioning
confidence: 99%
“…[1][2][3] Children in child care center settings have more upper respiratory infections, diarrheal illness, ear infections, and myringotomy tube placement than children who stay at home exclusively. [4][5][6][7] Previous research demonstrates that ill children are routinely excluded from child care unnecessarily given that most child care-related illnesses are minor in severity. [8][9][10][11] Unnecessary exclusions place a substantial burden on working families, businesses, and health care resources.…”
mentioning
confidence: 99%